RESISTANCE MECHANISM STUDIES IN SELECTED RICE GENOTYPES AGAINST BROWN PLANTHOPPER, NILAPARVATA LUGENS (STAL) - B , ANUSHA (The Journal of Research ANGRAU, 2026)
Twelve identified rice genotypes along with susceptible check (TN 1) and resistant check (PTB 33) were investigated for resistance against BPH during rabi 2021-22 at Regional Agricultural Research Station, Maruteru, Andhra Pradesh. Preference/non-preference mechanism was assessed through honeydew excretion studies and tolerance was measured through number of days to wilt. Brown planthopper fed on these genotypes excreted significantly lower quantity of honeydew than the susceptible TN 1 (529.33 mm2). Among the genotypes, PTB 18 and HWR-21 IR 71033-121-15-B recorded minimum honeydew excreted area of 91.00 mm2 and were equivalent with the resistant check (78.67 mm2). The number of days taken by the genotypes to wilt ranged from 21.33 to 34.67 days. The susceptible check TN 1 and resistant check PTB 33 took 21.33 and 34.67 days to wilt respectively. Among the genotypes, MTU 2837-31-1-1-1 took longer (32.33 days) to wilt followed by PTB 18 which took 30.33 days.